2010
DOI: 10.11613/bm.2010.031
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of metabolic syndrome in a local population in India

Abstract: 1 In sti tu te of Re sear ch in Scien ce and Me di ci ne, Sa lem, In dia 2 In sti tu te of Car dio lo gy, Ban glo re, In dia 3 De par tme nt of Bioc he mis try, Al Arab Me di cal Uni ver si ty, Ben gha zi, Li bya *Cor res pon di ng aut hor: dhas ta gir @ya hoo.ca Ab stra ctIn tro duc tion: Peop le wi th meta bo lic syndro me are about twi ce as li ke ly to de ve lop ce reb ro vas cu lar di sea se (CVD) and over four ti mes as li ke ly to de ve lop type 2 dia be tes com pa red to sub jec ts wit hout me ta bo li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…(12,13) In this light, it is possible to interpret the results of studies that have shown associations between increased MPV with target organ damage in patients with hypertension and diabetes, (14,15) and also in patients with acute coronary syndrome. (19,20) As in acute coronary syndrome, in which rupture of the fibrous cap allows contact of the platelets with the highly thrombogenic necrotic core, (19,20) vascular damage, caused by multiple CV risk factors, enables contact between platelets and thrombogenic substances even in asymptomatic patients. In both cases, the result is platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…(12,13) In this light, it is possible to interpret the results of studies that have shown associations between increased MPV with target organ damage in patients with hypertension and diabetes, (14,15) and also in patients with acute coronary syndrome. (19,20) As in acute coronary syndrome, in which rupture of the fibrous cap allows contact of the platelets with the highly thrombogenic necrotic core, (19,20) vascular damage, caused by multiple CV risk factors, enables contact between platelets and thrombogenic substances even in asymptomatic patients. In both cases, the result is platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…Total cholesterol, HDL, LDL and triglycerides were determined by chromatography (accessories Boeringher Mannheim). Reference values for serum lipid profile and fasting glucose were determined on the basis of The International Diabetes Federation (IDF) diagnstic criteria for MetSy (4).…”
Section: E X a M I N E E S A N D M E T H O D Smentioning
confidence: 99%
“…It has been estimated that 17-25% of the world population have MetSy, and the importance of the metabolic syndrome lies largely in the development of cardiovascular diseases and type 2 diabetes mellitus (3). Genetic factors, aging, hormonal factors and proinflammatory conditions may affect the occurrence of MetSy (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory marker CRP has recently been shown to be an independent risk for cardiovascular and peripheral arterial disease (30–32) and a pathogenic factor leading to endothelial dysfunction in the cell culture model (33). Moreover, elevated concentration of CRP has been associated with an increased risk for hypertension (34), and for type 1 and type 2 diabetes mellitus (35).…”
Section: The Role Of Inflammation In the Pathogenesis Of Amdmentioning
confidence: 99%